2020
DOI: 10.11628/ksppe.2020.23.2.233
|View full text |Cite
|
Sign up to set email alerts
|

Keyword Analysis of Arboretums and Botanical Gardens Using Social Big Data

Abstract: This study collects social big data used in various fields in the past 9 years and explains the patterns of major keywords of the arboretums and botanical gardens to use as the basic data to establish operational strategies for future arboretums and botanical gardens. A total of 6,245,278 cases of data were collected: 4,250,583 from blogs (68.1%), 1,843,677 from online cafes (29.5%), and 151,018 from knowledge search engine (2.4%). As a result of refining valid data, 1,223,162 cases were selected for analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Choo (2020) identified the trends in consumption markets with focus on keywords related to 'solitary consumption', and Kim and Han (2019) analyzed the leisure trend using a semantic network. Previous studies conducted quantitative and focused analysis through keyword frequency analysis (Park and Bae, 2018;Park and Oh, 2019;Park and Yeon, 2020;Shin et al, 2020;Woo and Suh, 2021), and supplemented qualitative and auxiliary analysis through related keyword analysis. Recently, studies are conducted using quantitative and qualitative analysis through topic modeling Park et al, 2021).…”
Section: Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Choo (2020) identified the trends in consumption markets with focus on keywords related to 'solitary consumption', and Kim and Han (2019) analyzed the leisure trend using a semantic network. Previous studies conducted quantitative and focused analysis through keyword frequency analysis (Park and Bae, 2018;Park and Oh, 2019;Park and Yeon, 2020;Shin et al, 2020;Woo and Suh, 2021), and supplemented qualitative and auxiliary analysis through related keyword analysis. Recently, studies are conducted using quantitative and qualitative analysis through topic modeling Park et al, 2021).…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Text mining studies had been used to identify massive research trends (Park and Bae, 2018 ;Byeon and Seo, 2020;Park et al, 2021;Choi and Choi., 2021) but recently they are actively conducted to identify the trends through perception changes and issues based on user experience (Kim, 2015;Kim and Jeon, 2018;Chae et al, 2021;Woo and Suh, 2018;Kong and Wang. 2019;Park and Oh, 2019;Do et al, 2020;Park and Yeon, 2020;Shin et al, 2020;Woo and Suh, 2020;Woo and Suh, 2021). Therefore, this study examines the changes in the main keywords of each type of green infrastructure before and after COVID-19 through blog text mining, derives key topics related to 'coronavirus', and analyzes related keywords, thereby capturing the changes in the cultural trend of use and providing policy implications.…”
Section: Introductionmentioning
confidence: 99%
“…Looking at the research trends related to Instagram data, Kim et al (2019) utilized Instagram's big data to determine the potential and importance of Instagram as a new tool in the field of regional survey and analysis as well as a data source from the perspective of urban users. Shin et al (2020) analyzed the original news text with a data mining technique using big data to understand how the public's interest in arboretums and botanical gardens has changed socially, economically, and culturally according to the trend of the times. Seo et al (2020) investigated how information about the Seoul Botanic Park is shared and propagated on the online system, and how recipients of such information perceive it, and reported that spatial information online is delivered in various types of text through social networking services (SNS) that enable users to communicate, rather than unilaterally through the official website.…”
Section: Instagram Is a Social Networking Service (Sns) Officiallymentioning
confidence: 99%
“…Big data 1) analytics 1) Big data does not merely indicate data that is big in size, but actually is used in various fields, which is a suitable method to analyze consumer perceptions, trends, and market flows . Kim (2016) reviewed the public perception and awareness of forest healing with SNS big data, and Shin et al (2020) used big data to identify how the social, economic, and cultural perceptions of citizens change over time, with keywords such as arboretums and botanical gardens. As for big data analytics or perception analysis related to gardens, Jang (2014) limited the scope of perception analysis to Suncheonman International Garden Expo, the search scope to blogs, and the period to the duration in which the expo was held, and then came up with implications by identifying visitor preferences and perception on certain gardens and spaces.…”
Section: Introductionmentioning
confidence: 99%